2020
DOI: 10.1074/jbc.ra120.014692
|View full text |Cite
|
Sign up to set email alerts
|

Crystallographic snapshots of UDP-glucuronic acid 4-epimerase ligand binding, rotation, and reduction

Abstract: UDP-glucuronic acid is converted to UDP-galacturonic acid en route to a variety of sugar-containing metabolites. This reaction is performed by a NAD+-dependent epimerase belonging to the short-chain dehydrogenase/reductase family. We present several high-resolution crystal structures of the UDP-glucuronic acid epimerase from Bacillus cereus. The geometry of the substrate-NAD+ interactions is finely arranged to promote hydride transfer. The exquisite complementarity between glucuronic acid and its binding site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
11

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 50 publications
1
25
0
11
Order By: Relevance
“…As a first step in our investigation, we analyzed the catalytic conversion of UDP-GlcA into the 4-keto intermediate with MD and QM/MM metadynamics methods (see the Supporting Information for methods). MD simulations (600 ns) starting from the UDP-GlcA complex structure with BcUGAepi (enzyme from Bacillus cereus; PDB 6ZLD [5] ) showed the pyranosyl moiety in a relaxed 4 C 1 conformation throughout. The sugar hydrogen atom at C4 remains in proximity (2.6 Å distance on average) to the nicotinamide C4' atom (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a first step in our investigation, we analyzed the catalytic conversion of UDP-GlcA into the 4-keto intermediate with MD and QM/MM metadynamics methods (see the Supporting Information for methods). MD simulations (600 ns) starting from the UDP-GlcA complex structure with BcUGAepi (enzyme from Bacillus cereus; PDB 6ZLD [5] ) showed the pyranosyl moiety in a relaxed 4 C 1 conformation throughout. The sugar hydrogen atom at C4 remains in proximity (2.6 Å distance on average) to the nicotinamide C4' atom (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…[2,3] UDP-D-glucuronic acid (UDP-GlcA) 4epimerase (UGAepi; EC 5.1.3.6) catalyzes stereoinversion at the C4-position of UDP-GlcA to provide D-galacturonic acid for the synthesis of cell-wall polysaccharides. [4][5][6][7][8][9] UGAepi illustrates in many ways a general problem of fundamental importance in enzyme catalysis: in order to promote the reaction efficiently, the enzyme must achieve a fine balance between protein flexibility and precise substrate positioning. [6] The UGAepi reaction consists of two catalytic steps in a canonical sugar nucleotide epimerase mechanism, [3h, 10-15] such as that of UDP-galactose 4-epimerase (Figure 1): site-specific C4-oxidation of the substrate by a tightly bound NAD coenzyme; and non-stereospecific reduction of a transient UDP-4-ketohexuronic acid intermediate by the enzyme-Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Sun et al pointed out the importance of the positively charged R192 and the adjacent D194 (Streptomyces viridosporus UGAE), both located in the purple wall, which might interact and stabilize the negatively charged carboxylate moiety of the substrate (Sun et al, 2020). Recently, Borg et al (2020) characterized a novel UGAE from Bacillus cereus and demonstrated the importance of an hydrogen bond network composed of four residues, namely T126, S127, S128 (all yellow wall) and T178 (193 in the orange wall), in the coordination of the carboxylate substrate (Borg et al, 2020;Iacovino et al, 2020). In the CPa2E, the yellow wall contains the catalytically important Asn and Lys (personal communication).…”
Section: (Landscape Table)mentioning
confidence: 99%
“…HP3 flesh showed exclusive expression of the auxin-responsive protein SAUR19 ( Kathleen and Farquharson, 2014 ), zinc-binding dehydrogenase, non-specific lipid-transfer protein 3, vinorine synthase, and transferase family. HP4 flesh exclusively expressed trans -resveratrol di-O-methyltransferase and UDP-glucuronate 4-epimerase 5 ( Iacovino et al., 2020 ). These exclusively expressed genes may have affected the observed phenotypes.…”
Section: Discussionmentioning
confidence: 99%